2003
DOI: 10.1007/s00122-003-1294-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow estimation with microsatellites in a Malagasy seed orchard of Eucalyptus grandis

Abstract: Eucalyptus grandis has a mixed-mating reproductive system. Malagasy Eucalyptus seed orchards were established 15 years ago with two aims both based on panmixia: open-pollinated seed production and genetic improvement. The panmixia hypothesis has never been confirmed in the seed orchard. From a seedling seedorchard stand comprising 349 trees and using data obtained with six selected microsatellite markers, paternity analysis was performed for 724 offspring collected on 30 adult trees. Paternity assignment, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
3
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 29 publications
5
50
3
4
Order By: Relevance
“…In the present case, the large majority of the alleles (72%) in the 60 parental trees occurred at frequencies bellow 10%. This was also reported in studies inferring paternity in oak (Dow and Ashley, 1998;Streiff et al, 1999) and in Eucalyptus (Chaix et al, 2003). In the case of the 60 parental trees, only one locus was not in HWE, but relatedness among parental trees is not to be excluded, as was further confirmed by a sounding probability of biparental inbreeding.…”
Section: Genetic Variationsupporting
confidence: 69%
See 3 more Smart Citations
“…In the present case, the large majority of the alleles (72%) in the 60 parental trees occurred at frequencies bellow 10%. This was also reported in studies inferring paternity in oak (Dow and Ashley, 1998;Streiff et al, 1999) and in Eucalyptus (Chaix et al, 2003). In the case of the 60 parental trees, only one locus was not in HWE, but relatedness among parental trees is not to be excluded, as was further confirmed by a sounding probability of biparental inbreeding.…”
Section: Genetic Variationsupporting
confidence: 69%
“…This is a thorough hypothesis since the 60 plus trees used in the CSO were all selected within the same provenance: Leiria. In a similar study, three out of six SSR loci also displayed significant departures from the HWE (Chaix et al, 2003) both in the parental trees and in the progeny. In the current study, the fixation index was found to be much higher in the progeny (0.239) than in the parental population (0.091) and in a population from the provenance where the trees were selected (Leiria: 0.003, data from Derory et al 2002 using the same three loci).…”
Section: Genetic Variationmentioning
confidence: 66%
See 2 more Smart Citations
“…Observed heterozygosity (individual heterozygosity), however, was consistently higher in the breeding population than in native trees, suggesting that heterozygotes have been preferentially selected within the program . Markers have been successfully used to estimate outcrossing rates, study parentage, and outside pollen contamination in seed orchards, parameters that have also been valuable to provide general guidelines for risk assessment of gene flow from plantation to natural stands (Barbour et al 2010;Burczyk et al 2002;Chaix et al 2003;Gaiotto et al 1997;Jones et al 2008;Patterson et al 2004;Rao et al 2008). In breeding programs, DNA paternity testing was successfully employed to retrospectively select parents of higher specific combining ability and demonstrate realized gains in volume growth above 24% in commercial forest stands (Grattapaglia et al 2004b).…”
Section: Molecular Breedingmentioning
confidence: 99%